3
$\begingroup$

Suppose that for every $n ∈ N$, $a_n > 0$ and set $b_n = \frac{a_{n+1}}{ a_n}$ and $c_n = (a_n)^{1/ n }$. Prove that if $b_n → L$ then $c_n → L$. Is the converse true.

If $a_n \to \infty$ then $b_n \to 1$ and similarly $c_n \to 1$

So it's easy to see this is the case. Seems like the squeeze theorem is the trick here. But I know $\neg(c_n \le b_n), \forall a_n$

but maybe: $ ??\le (a_n)^{1/n} \le (a_n)^{1/n} \cdot \frac{a_n+1}{a_n} $

$\endgroup$
  • 2
    $\begingroup$ Did you mean $b_n=\frac{a_{n+1}}{a_n}$? $\endgroup$ – Ángel Mario Gallegos Oct 6 '15 at 2:39
  • $\begingroup$ oh yes I do, looked at it wrong $\endgroup$ – oliverjones Oct 6 '15 at 2:40
  • 1
    $\begingroup$ assuming Mario G's correction, its not clear to me that $a_n \to \infty \implies b_n \to 1$ $\endgroup$ – user237392 Oct 6 '15 at 2:44
  • $\begingroup$ @bey I deleted that part after editing. $\endgroup$ – oliverjones Oct 6 '15 at 2:47
3
$\begingroup$

We give a semi-formal argument, for positive $L$. A slightly simpler argument works for $L=0$.

Let $\epsilon$ be very small positive, much smaller than $L$. There is an $N$ such that if $n\ge N$ then $L-\epsilon/2\lt \frac{a_{n+1}}{a_n}\lt L+\epsilon/2$.

It follows that for any $m$ we have $$a_N(L-\epsilon/2)^{m}\lt a_{N+m}\lt a_N(L+\epsilon/2)^m.$$ Take the $(N+m)$-th root. If $m$ is large enough, $a_N^{1/(N+m)}(L-\epsilon/2)^{m/(N+m)}$ is larger than $L-\epsilon$, and $a_N^{1/(N+m)}(L+\epsilon/2)^{m/(N+m)}$ is smaller than $L+\epsilon$.

So given $\epsilon\gt 0$, for large enough $k$ we have that $a_k^{1/k}$ is within $\epsilon$ of $L$.

Remark: The converse does not hold. Let $a_n=1$ if $n$ is odd, and let $a_n=2$ if $n$ is even.

$\endgroup$
  • $\begingroup$ This is a good approach that avoids the appeal to Stolz-Ceasaro, which the OP likely has not seen yet. +1 $\endgroup$ – Mark Viola Oct 6 '15 at 3:18
2
$\begingroup$

Let $x_n=\log b_n\to \log L$, then $$\log c_n=\frac{C+x_1+\cdots+x_n}n$$ for some constant C. We have a direct case of Cesaro mean.

$\endgroup$
  • $\begingroup$ This is a very efficient approach. So, +1. As a suggestion for improvement, you might consider expanding the explanation. That is, we can show that $\log c_n =\cdots $ from the fact that $a_2=b_1a_1$, $a_3=b_2a_2=b_2b_1a_1$ ... $a_n=a_1b_1b_2\cdots b_{n-1}$. Then, continue ... Make sense? $\endgroup$ – Mark Viola Oct 6 '15 at 3:16
1
$\begingroup$

Hint: Use the classical result whose proofs have been asked at least one time here: If $(a_{n})$ is a sequence of $a_{n} > 0$, then $$ \liminf \frac{a_{n+1}}{a_{n}} \leq \liminf_{n \to \infty}a_{n}^{1/n} \leq \limsup a_{n}^{1/n} \leq \limsup \frac{a_{n+1}}{a_{n}}. $$ From this it follows immediately that if $\lim_{n \to \infty}a_{n+1}/a_{n}$ exists and $=l$ for some $l \in \mathbb{R}$, then $\lim_{n \to \infty}a_{n}^{1/n}$ exists and $=l$.

$\endgroup$
  • $\begingroup$ how do we obtain the first inequality? $\endgroup$ – Nighty Oct 21 '15 at 14:43

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.